Effects of five tissue sources of silver carp by-products on the structure, physicochemical and emulsifying properties of gelatin - Guangyi Kan; Li Li; Huan Gong; Lijia Chen; Xichang Wang; Jian Zhong (Current Research in Food Science)
The effects of tissue sources on gelatin's physicochemical and functional properties remain unclear. This work aimed to analyze the effects of five tissue sources on the properties of fish gelatins. Five gelatins were extracted from different silver carp by-products (skin, scale, fin, head, and bone) and the effects of tissue sources on the gelatin's properties were studied. The gelatin's β-sheet percentages and total sodium dodecyl sulfate-polyacrylamide gel electrophoresis band intensities (β, α1, and α2 chains) showed similar dependence to the tissue sources: skin ≈ scale > fin ≈ head > bone. Bone-related gelatins (from head and bone) showed lower water-holding capacity and fat-binding capacity values than the other gelatins. Tissue sources significantly affected the gelatin's gel strength values: skin ≈ fin > scale > bone ≈ head. Scale and bone gelatin solutions had significantly lower rheological apparent viscosities than other by-product gelatin solutions. The interfacial tension and rheological apparent viscosity values of the fish oil-loaded gelatin-stabilized emulsions depended on the gelatin tissue sources and gelatin concentrations. In particular, skin, scale, and fin gelatins induced no obvious emulsion creaming at the gelatin concentration of 10 g/L during the emulsion storage. Bone-related gelatins induced higher emulsion creaming index values for the emulsions with 10 g/L of gelatins during the emulsion storage. This work confirmed tissue sources could significantly affect the properties of gelatins. Five tissue sources had different effects on the structural, physicochemical, and emulsifying properties of silver carp by-product gelatins. Especially, the gelatins from different silver carp by-products showed different water-holding and fat-binding capacities, gel strengths, interfacial tension, rheological apparent viscosities, and emulsion stabilization abilities. These properties are important considerations for the application of silver carp by-product gelatins in food and other industries.